2021
DOI: 10.1371/journal.pone.0252963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social distancing on the spread of common respiratory viruses during the coronavirus disease outbreak

Abstract: During the coronavirus disease (COVID-19) pandemic, social distancing was effective in controlling disease spread across South Korea. The impact of national social distancing on the spread of common respiratory virus infections has rarely been investigated. We evaluated the weekly proportion of negative respiratory virus polymerase chain reaction (PCR) test results and weekly positive rates of each respiratory virus during the social distancing period (10th–41st weeks of 2020) and the corresponding period in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…According to other studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 25 , 26 ], our results show that the circulation of respiratory viruses was disrupted during the pandemic, even if the magnitude of this effect was different between the viruses analyzed.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…According to other studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 25 , 26 ], our results show that the circulation of respiratory viruses was disrupted during the pandemic, even if the magnitude of this effect was different between the viruses analyzed.…”
Section: Discussionsupporting
confidence: 78%
“…These preventive strategies, in particular physical distancing and the use of masks, may have contributed to reducing the circulation of other respiratory viruses besides SARS-CoV-2 [ 12 , 13 ]. Different studies show that social restrictions had an impact on the spread of both seasonal influenza [ 14 , 15 , 16 , 17 , 18 ] and other respiratory viruses [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several researchers reported that the NPIs for COVID-19 suppressed the outbreak of common respiratory virus infections as well as that of COVID-19. 6 7 8 9 10 11 12 13 14 The outbreaks of common respiratory virus infections are not directly affected by the COVID-19 vaccination rate or the emergence of SARS-CoV-2 variants; hence, the data of common respiratory virus infection outbreaks help determine the effect of NPIs without being affected by other factors related to the COVID-19 outbreak. Among the common respiratory viruses, non-enveloped viruses such as rhinovirus (RV), human bocavirus (BOV), and adenovirus (ADV) are continuously detected despite the implementation of NPIs during the COVID-19 pandemic, because they are more resistant to environmental challenges or alcohol-based disinfectants than enveloped viruses and can be easily transmitted through not only respiratory droplets but also contacts with unwashed hands.…”
Section: Introductionmentioning
confidence: 99%
“…Among the common respiratory viruses, non-enveloped viruses such as rhinovirus (RV), human bocavirus (BOV), and adenovirus (ADV) are continuously detected despite the implementation of NPIs during the COVID-19 pandemic, because they are more resistant to environmental challenges or alcohol-based disinfectants than enveloped viruses and can be easily transmitted through not only respiratory droplets but also contacts with unwashed hands. 9 10 14 In particular, the incidence of RV infection decreased when the NPIs were strongly implemented but suddenly increased when the implementation of NPIs was relaxed. 14 15 16 Because of such distinct inverse relationship between the incidence of RV and intensity of NPI implementation during the COVID-19 pandemic, the incidence of RV was suggested as an indicator of the effect of NPIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation